#TITLE_ALTERNATIVE# - SEMIDANG PUTRA (NIM : 13206039); Pembimbing : Dr. Effrina Yanti Hamid, ST. MT., ADHIPTA
Digital Video Broadcasting Terrestrial (DVB-T) uses Orthogonal Frequency Division Multiplexing (OFDM) as its multiplexing technique in which a high rate serial data is converted to lower rate parallel data in n- orthogonal subcarrier. DVB-T transmission through wireless channel with its characteristics can cause received signal degradation. Therefore, acquired signal at DVB-T receiver should be compensated with channel estimation and equalization. DVB-T transmission parameter standard recognizes pilot symbol insertion technique, including continual pilot insertion and scattered pilot insertion. Channel estimation is applied based on pilot symbol insertion technique with interpolation technique to reveals channel response coefficient. In this final project, both linear and spline interpolation technique was analyzed as channel estimators at DVB-T receiver. Least Square (LS) algorithm was applied as equalization technique. Two estimators performance were assessed based on BER (Bit Error Rate) vs. Eb/No curves. Two Rayleigh fading channel was implemented to test both estimators. The simulation results showed at Eb/No= 30 dB, channel estimation with spline interpolation can compensate BER reaching 2,2x10-3 in the first fading channel as well as 2,4x10-3 in the second fading channel. However, channel estimation with linear interpolation at Eb/No= 30 dB, can only compensate BER reaching 1,61x10-2 in the first fading channel and 1,64x10-2 in the second fading channel.